A comparative study on nanoscale mechanical properties of CrMnFeCoNi high-entropy alloys fabricated by casting and additive manufacturing - Siqi Liu; Di Wan; Shuai Guan; Yuequn Fu; Zhiliang Zhang; Jianying He (Journal of Materials Research and Technology)
Additive manufacturing (AM) has emerged as a pioneering method for fabricating high entropy alloys (HEAs), yet a comprehensive comparison of their nanoscale mechanical properties with those produced by the conventional casting method remains unexplored. In this study, the nanoindentation was utilized to investigate the nanoscale elastic and plastic characteristics in both additive-manufactured (AM-ed) and as-casted single-phase face-centered cubic (FCC) equiatomic CrMnFeCoNi HEAs. Herein, the hardness, reduced modulus, indentation size effect (ISE), yield strength, fracture toughness, and strain rate sensitivity were comprehensively investigated. The results indicated that the hardness of AM-ed HEA was higher than the as-casted HEA, and the reduced modulus values showed no notable distinction between the two samples. The AM-ed HEA demonstrated simultaneous enhancements in yield strength and fracture toughness compared to the as-casted HEA. The as-casted HEA possessed a more distinct indentation size effect (ISE) than the AM-ed HEA. It was observed that the AM-ed HEA exhibited relatively lower strain rate sensitivity and a larger activation volume. This direct comparison of the mechanical properties and deformation mechanisms from a nanoscale view offers unique insights for optimizing and advancing AM techniques in the fabrication of HEAs.